Taska Excel kids / Nur Liyana Bakarudin ... [et.al.]. - Bakarudin, Nur Liyana; Md Said, Rabiatul Ain; Ismady, Farah Aida; Zahari, Nurhidayatul Amira; Ismail, Siti Maryam (2012)
Taska Excel Kids is the name that has been decided on the form of all the partnerships. Each partner has contributes certain amount of capital as agreed in our agreement. Our main business activity is childcare. We will open our business at No.4, Lorong Unigarden 7B, Taman Unigarden, 94300, Kota Samarahan, Sarawak and hopefully will open by 1st January 2013. All partners are encourage and entitled to participate in all business management. We have agreed that Nur Liyana Binti Bakarudin as the Manager, Nurhidayatul Amira Binti Zahari as the Head of Administration, Siti Maryam Bini Ismail as the Head of Operational, Farah Aida Binti Ismady as the Head of Marketing and Rabiatul Ain Binti Md Said as the Head of Financial. The management team will be lead by the Manager and the other heads will help in other process. The manager is responsible in controlling, leading, organizing as well as plan the entire business. The Head of Administrative will responsible in doing for all jobs relating to office administration. The Head of Marketing will responsible in preparing the marketing process which includes the process of identifying the target market, determining the market size, identifying the competitors, determining the market share, developing the sales forecast and marketing strategies. The operation of our business is controlled and monitored by the Head of Operation. This is where quality control and productivity will take place in order to improve the efficiency of the workers. Finally, the Head of Financial will handle financial matters such as preparing for the budgets and financial statement for the each department. All the financial statement need to be taken care properly by our Head of Financial.